The Effect of Brand Equity on Brand Loyalty to Skincare Products Mediated By Customer Satisfaction - Idemon, Anggia Febriyana; Chairun Nisa, Puspita (PARADIGMA : JURNAL ILMU PENGETAHUAN AGAMA, DAN BUDAYA, 2024)
Maintaining and increasing brand loyalty is paramount due to a decrease in product differentiation and an increase in product market uncertainty. Therefore, brand loyalty is a measure of a company's business performance that affects the market share of a product. The purpose of this study is to explore the effect of brand equity and brand loyalty on mediated by customer satisfaction and to confirm the significant dimensions of brand equity. The population of this study are Scarlett skincare users who live in Jakarta and Bekasi whose numbers are unknown. Respondents of this study were 115 respondents with the criteria of Scarlett skincare users aged 17-30 who have bought and used Scralett Skincare in the last 6 months. The analysis method used is Partial Least Square Structural Equation Modeling. The results stated that perceived quality and perceived cost value can increase customer satisfaction, perceived quality and customer satisfaction have a positive effect on brand loyalty, however, brand identification, brand trust and lifestyle alignment have no effect on customer satisfaction. Perceived quality and perceived cost value on brand loyalty are mediated by customer satisfaction, while brand identification, brand trust and lifestyle alignment are not proven. Future research is expected to expand the range of regions and add other variables related to brand loyalty such as brand image.